Terminology Matters: A Review on the Concept of Economic Predation. Issue 4 (2nd October 2022) - Mesly, Olivier; Petrescu, Maria; Mesly, Alexandra
Abstract: This article compares various disciplines to show that the concept of predation is associated with notions that are relevant to the economic domain, such as equilibrium, risks, and hidden societal costs. We review the economic literature in some of the top-ranked economic journals on the subject of predation dating back a hundred years. Our analysis shows that economic academics use the concept of predation differently and at times in an erroneous or overly narrow way. This article argues that economic theory must take into consideration predator-prey dynamics during one-on-one interactions between sellers acting as predators of sorts by using information asymmetry to their advantage, and their prey in the form of naïve clients, who undergo economic/financial harm as a result. We propose that a better understanding of the concept of predation may enhance the drafting of government policies. To our knowledge, this is the first article that examines the concept of predation in its original sense across the literature and across decades and that demonstrates its relevance in economic theory.